Platelets, thrombo-inflammation and cancer - E. V. Slukhanchuk; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; A. G. Solopova; V. N. Galkin; A. S. Shkoda; V. I. Tsibizova; V. I. Linnikov; Ismail Elalamy; J.-С. Gris; B. Brenner; et al. (IRBIS LLC, 2022)
It has long been recognized a crucial role played by platelets in thrombosis and hemostasis. Along with that, laboratory and clinical data suggest that platelets contribute to tumor progression and metastasis through a variety of interactions with cancer cells. During oncological process, the platelet function becomes modulated via their activation and increased aggregation being one of the risk factors for developing thrombosis in cancer patients. The platelets per se enhance tumor cell dissemination, activate endothelial cells, and attract immune cells to the primary and metastatic tumor sites. In this review, we summarize the current knowledge about the complex interactions between platelets and tumor cells, as well as cells of the microenvironment, and discuss the development of new antitumor agents aimed at various arms in platelet functioning.